2017
DOI: 10.1007/s12032-017-1048-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a frozen section analysis of the ureteral margin in bladder cancer patients treated with radical cystectomy and neoadjuvant chemotherapy

Abstract: Although the clinical utility of a frozen section analysis (FSA) at the time of radical cystectomy (RC) has already been established, its significance and utility in bladder cancer patients receiving neoadjuvant chemotherapy (NAC) have not yet been fully evaluated. We identified 458 patients (937 ureters) who underwent open RC for bladder cancer at our 7 Japanese institutions between 2004 and 2015. Among these patients, 139 (284 ureters) received NAC before RC (NAC group), while 319 (653 ureters) underwent RC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Table 1 summarizes the characteristics of included studies. Fourteen studies, comprising 8208 patients, were included in the quantitative synthesis [7,13,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the characteristics of included studies. Fourteen studies, comprising 8208 patients, were included in the quantitative synthesis [7,13,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Ten studies provided data on the value of pathologic detection of malignant involvement of the ureter on FSA during RC [13,[21][22][23][24][25][26][27][28]33]. The prevalence of ureteral malignant involvement on FSA and final margin analysis varied from 0.85% (in patients without concomitant CIS) [32] to 35.6% (in patients with concomitant CIS) [32] and from 5.4% [28] to 15% [21], respectively.…”
Section: Ureteral Marginsmentioning
confidence: 99%
“…Various studies have assessed the diagnostic accuracy of FSA for ureteral margins by comparing with the final histopathology (i.e., frozen section control). In some of these studies, the sensitivity and specificity of FSA for the diagnosis of CIS, urothelial carcinoma, and/or severe dysplasia ranged 45%–89% and 83%–99.8%, respectively 8,10–15 . It has also been documented that 28%–83% of cases with initial abnormal FSA could be converted to a final negative margin by additionally excising ureteral tissue 8,10,12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, patients with positive FSA have been shown to have a significantly higher risk of tumor progression or disease‐specific mortality in univariate models, but not in multivariate settings 10,11,14 . Positive FSA diagnosis also tended to correlate with tumor recurrence in patients undergoing neoadjuvant chemotherapy prior to radical cystectomy ( N = 68; p = 0.073), but not in those without neoadjuvant therapy ( N = 111; p = 0.931) 15 . In a more recent study involving 98 patients/196 ureteral FSAs, positive FSA was found to be an independent risk factor for overall survival (hazard ratio [HR] = 4.2; p = 0.016) 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation